Professional Development of Elementary School Teachers - Moretti, Melita; Ropar, Ivan; Moretti, Adi (Naše gospodarstvo/Our economy, 2013)
Knowledge societies make new demands and expectations of teachers that require changes in their roles and abilities. Teachers must be open to change, prepared to improve their qualifications, and motivated for constant professional development. This also requires the support of head teachers. Through quantitative research, we were able to get a closer look at the opinions elementary school teachers have of their own possibilities for professional development as well as the obstacles they face along the way. The results of the research were compared with theoretical fin- dings, and directions and recommendations for practice were suggested.
Keywords: Teacher; elementary school; career; development; work experience